1716d Effects of olfactory stimulus by odour on cerebral blood flow and peripheral blood oxygen levels in multiple chemical sensitivity. (24th April 2018) - Azuma, K; Uchiyama, I; Tanigawa, M; Bamba, I; Azuma, M; Takano, H; Yoshikawa, T; Sakabe, K
Abstract : Introduction: Multiple chemical sensitivity (MCS), often called idiopathic environmental intolerance, is a chronic acquired disorder characterised by nonspecific symptoms attributed to exposure to common odorous chemicals. We previously reported significant activations in the prefrontal cortex (PFC) during olfactory stimulation using several different odorants in patients with MCS compared with controls. Previous clinical observations demonstrated differences in oxygen partial pressure in peripheral venous blood between patients with MCS and controls. Our objective is to investigate peripheral blood oxygen levels during olfactory stimulation to characterise patients with MCS. Methods: We investigated changes in the prefrontal area using near-infrared spectroscopic (NIRS) imaging and those in peripheral arterial blood oxygen saturation (SpO2 ) using a pulse oximeter during olfactory stimulation with odorants (γ-undecalactone) at three concentrations (zero, odour recognition threshold, and normal perceived odour level) in 11 patients with MCS and 10 controls. We also examined their oxygen partial pressures in peripheral venous blood at normal condition before the test. Results: We observed significant activations in the PFC during olfactory stimulation in patients with MCS. The SpO2 in peripheral arterial blood in patients with MCS remained higher than that in controls during olfactory stimulation tests. The SpO2 remarkably decreased in patients with MCS compared with that in controls during olfactory stimulus at normal perceived odour level and the recovery of the SpO2 after the stimulus was delayed in these patients. No significant differences in oxygen partial pressures of peripheral venous blood were observed. Conclusion: Patients with MCS exhibited stronger brain responses to odours at normally perceived levels. Changes in SpO2 in the peripheral arterial blood suggest that MCS might result in poor oxygen supply to the peripheral tissues or inadequately control the oxygen supply.